Analog Structural Modeling Of Resonant Tunneling Diode Using Ltspice - Zaharimying, Wan Nurnabilah (Universiti Sains Malaysia, 2017)
In this research, the material InGaAs/AlAs and GaAs/AlAs are used as the material for the double barriers resonant tunneling diode (RTD). RTD is the fastest electronic device to date. RTD consists of a quantum well sandwiched in between two thin barriers InGaAs/AlAs and GaAs/AlAs. Both ends are terminated with a highly doped semiconductor to provide electrical contacts. The operation of RTD physical model requires extremely long calculation time. For circuit design, this model can effectively be described in analog structural modeling using LTspice. One of the ways to implement the built-in model for an RTD is by using lookup table method in the voltage controlled current source. In the circuit representative of RTD, the value of device parameter had been calculated and simulated to get the IV curve. IV curve had been simulated to match the modeled and measured curve which obtained from the previous work by Zawawi et. al [3] in 2015 to extract the structural parameters of the device. The study on device simulation on the circuit representation was important as well in order to bring RTD in real applications which is one of the objectives of the work. The simulation of circuit applying the purposed RTD model in this work was a success in proving the theory of RTD device shows that, different materials of RTD will produce a different peak to valley current ratio (PVCR) while correspond well with the theory of RTD device.